Penerapan Model Pembelajaran Berbasis Masalah untuk Meningkatkan Kemandirian Belajar Siswa - Yeni Rahmawati (FONDATIA, 2017)
As one institution that provides formal education, schools have a very important role in realizing the goals of national education through the process of teaching and learning. The education has a function, (Law No.20 of 2003 article 3) is as follows: National Education functions to develop the ability and shape the character and civilization of the nation that is useful inorder to educate the nation's life, aiming for the potential of students to become learners who believe , fear God, be noble, healthy knowledgeable, creative, independent and become a democratic and responsible citizen. The methods used in Data Collection are Interview Method, Observation Method, Documentation Method and Method of Questionnaire. Based on the results of the questionnaire score of students learning independence class IX on the first cycle has been tiggi 67.5% and 32.5%. Students who scored 44-62 as many as 13 people and students who scored 63-81 as many as 27 people so that classically obtained an average score of 65.62. In cycle II obtained data that there are 5% of students who already have a very high learning independence, 72.5% students with high independence and 22.5% of students have less high learning independence. Students who scored 44-62 as many as 9 people, students who scored 63-81 as many as 29 people, and students who scored 82-100 as many as 2orang so obtained a score of 67.45.